Formulation and Evaluation of Topical Dosage Forms Containing Niacinamide - Pártos, Péter; Bakhtiari, Helia; Pető, Ágota; Kósa, Dóra (De Remediis, 2025)
This study focuses on the formulation and evaluation of a cream and gel containing niacinamide, a commonly used active ingredient in skincare. Niacinamide, a water-soluble form of vitamin B₃, is known for its ability to strengthen the skin barrier, reduce inflammation, and regulate sebum production. Two formulations were developed: a cream composed of cetyl stearyl alcohol, stearic acid, glycerol, isopropyl myristate, sucrose ester, propylene glycol, distilled water, and niacinamide; and a gel formulated with glycerol, carbopol, triethanolamine, distilled water, and niacinamide. The cream, an oil-in-water emulsion, was designed for rich, long-lasting moisturization, while the gel was intended as a lightweight, water-based alternative. Both formulations were analyzed for pH, texture, dissolution and potential toxicological properties. The results revealed distinct differences: the cream provided superior hydration and barrier repair, whereas the gel offered a non-greasy, refreshing texture more suitable for oily or combination skin types. These findings highlight the versatility of niacinamide in topical applications and establish a foundation for further research on its efficacy in different delivery systems.